2012
DOI: 10.1111/j.1399-5618.2012.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders in offspring of parents with bipolar and major depressive disorders

Abstract: These findings provide unique information on the broad manifestations of parental mood disorders in their offspring. The earlier onset and increased risk of recurrent MDD in the offspring of parents with BPD compared to those of controls suggests that the episodicity characterizing BPD may emerge in childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 43 publications
10
68
3
5
Order By: Relevance
“…First, this study extends previous reports in demonstrating that young subjects at high genetic risk for BD were also at significantly increased risk for developing a broad range of psychopathology (Birmaher et al, 2009;Duffy et al, 2010;Duffy et al, 2014;Hillegers et al, 2005;Leopold et al, 2014;Nurnberger et al, 2011;Vandeleur et al, 2012;Wals et al, 2001;Whalley et al, 2011). Specifically, we found that AR subjects were more likely to develop depressive, anxiety and behavioural disorders compared to controls.…”
Section: Accepted Manuscript 13supporting
confidence: 85%
See 2 more Smart Citations
“…First, this study extends previous reports in demonstrating that young subjects at high genetic risk for BD were also at significantly increased risk for developing a broad range of psychopathology (Birmaher et al, 2009;Duffy et al, 2010;Duffy et al, 2014;Hillegers et al, 2005;Leopold et al, 2014;Nurnberger et al, 2011;Vandeleur et al, 2012;Wals et al, 2001;Whalley et al, 2011). Specifically, we found that AR subjects were more likely to develop depressive, anxiety and behavioural disorders compared to controls.…”
Section: Accepted Manuscript 13supporting
confidence: 85%
“…The odds of an affective disorder were 4.9 times greater for those living in a single parent home than for those living with both biological parents. This is consistent with a finding from a Swiss high-risk study (Vandeleur et al, 2012) which found that lower rates of affective disorders in AR offspring were associated with living with both biological parents, and is in line with the broader literature on the increased rate of later mental illness in children who were exposed to parental marital disruption during their developmental years (Gilman et al, 2003;Strohschein et al, 2005;Cherlin et al, 1998). However, as our findings are cross-sectional we cannot exclude the alternative possibility that the disruption in the parental relationships may be due to the impact of severe affective illness in these families.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…La media de edad de los individuos en el momento de la evaluación era 17,3 ± 6 (6-30) años, y la escolaridad, 8,5 ± 4,1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) años. Del total de la muestra, el 54,6% (n = 59) provenía de zonas urbanas.…”
Section: Resultsunclassified
“…Estas investigaciones también han evidenciado un inicio más temprano de psicopatología general y un mayor número de episodios de trastornos afectivos 2,3,9,10 . En otros estudios, la tasa de trastornos disruptivos no ha sido más alta que en los grupos controles o la población general [29][30][31] .…”
Section: Discussionunclassified